Вплив відпалу на інтенсивність термолюмінесценції KY3F10 : Ho3+ - Debelo, N. G.; Hailemariam, S. (Publishing house "Academperiodika", 2020)
The effect of thermal annealing on thermoluminescence (TL) glow curves of commercially obtained KY3F10:Ho3+ phosphor is investigated, and the result is compared with that of unannealed sample. The samples were annealed at different annealing temperatures: namely, 400, 500, and 600 ∘C. The activation energy (trap depth), which is one of the TL kinetic parameters, is calculated for the annealed and unannealed samples using the variable heating rate (VHR) method. The results show that the thermal annealing has a clear effect on the TL intensities of the glow curves. The maxima of the TL glow curves shift toward a higher temperature region, as the annealing temperature increases. Moreover, the higher the annealing temperature, the shallower the position of the trap beneath the edge of the conduction band. The X-ray diffraction (XRD) pattern of the sample shows a monoclinic structure with unit cell dimensions (in Angstr¨om) a = 10.41, b = 6.73, c = 12.46 match with JCPDS card No. 21-1458.